Learning to argue: A study of four schools and their attempt to develop the use of argumentation as a common instructional practice and its impact on students. Issue 3 (17th January 2013) - Osborne, Jonathan; Simon, Shirley; Christodoulou, Andri; Howell‐Richardson, Christina; Richardson, Katherine
Abstract This article reports the outcomes of a project in which teachers' sought to develop their ability to use instructional practices associated with argumentation in the teaching of science—in particular, the use of more dialogic approach based on small group work and the consideration of ideas, evidence, and argument. The project worked with four secondary school science departments over 2 years with the aim of developing a more dialogic approach to the teaching of science as a common instructional practice within the school. To achieve this goal, two lead teachers in each school worked to improve the use of argumentation as an instructional practice by embedding activities in the school science curriculum and to develop their colleague's expertise across the curriculum for 11‐ to 16‐year‐old students. This research sought to identify: (a) whether such an approach using minimal support and professional development could lead to measurable difference in student outcomes, and (b) what changes in teachers' practice were achieved (reported elsewhere). To assess the effects on student learning and engagement, data were collected of students' conceptual understanding, reasoning, and attitudes toward science from both the experimental schools and a comparison sample using a set of standard instruments. Results show that few significant changes were found in students compared to the comparison sample. In this article, we report the findings and discuss what we argue are salient implications for teacher professional development and teacher learning. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50:315–347, 2013